Pengembangan Potensi Desa Wisata Pasca Revitalisasi Sebagai Upaya Pemberdayaan Perekonomian Lokal: Studi Kasus Lembah Asri Serang Kabupaten Purbalingga - Nurafifah, Syifa Annisa; zaenuri, muchamad (Journal of Governance Innovation, 2025)
Efforts to develop tourism potential through tourism awareness groups are carried out because they see the potential of Serang Village. In particular, the potential of natural tourism has not been maximized, and there are also potential crafts, arts and culinary that are still not well managed.  In the context of developing tourism potential, there are several indicators to be able to realize the digitalization of tourist villages, including attraction, amenity, accessibility. The purpose of this research is to find out how efforts to develop tourism potential in Serang Village and the impacts caused after revitalization. The method used in this research is a qualitative analysis method using primary data sources. This research is a field research with a type of qualitative research that uses data collection techniques using observation, documentation and interviews and secondary from mass media news, journals, articles processed using Nvivo12 as a form of data visulization. The results showed that the development of tourism potential has been maximally utilized after revitalization starting from the development of attraction, accessibility, and amenity, where it has an impact on employment opportunities, ownership control and the economy which can be proven by an increase in village revenue, the level of tourist visits and a decrease in the unemployment rate in Serang Village.